2014
DOI: 10.1007/s00540-013-1786-2
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of multisensory rehabilitation on development of cognitive dysfunction following systemic inflammation in aged rats

Abstract: Systemic inflammation can trigger transient or longer-lasting cognitive impairments, particularly in elderly patients. However, its pathogenesis has not been sufficiently clarified. In this study, we explored the potential effects of multisensory rehabilitation on cognitive dysfunction following systemic inflammation using an animal model. Aged male Wister rats were randomly injected intraperitoneally with either saline (control) or lipopolysaccharide (LPS; 5 mg/kg). After injection, both groups of rats were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
11
2
Order By: Relevance
“…In the long-term group, cytokine and chemokine levels in LPS-treated and DSP4+LPS-treated rats were returned to control levels, suggesting a resolution of inflammation after seven days. While previous studies showed increased hippocampal IL-1β levels after LPS exposure in rats [ 65 , 66 ], this was not the case under our experimental conditions, possibly due to differences in animal models or incubation period between LPS administration and sample collection. It is also noteworthy that the LPS dose used in our study (0.75 mg/kg) was lower than the ones used in the Fu et al [ 65 ] (2 mg/kg) and Kawano et al [ 66 ] (5 mg/kg) studies.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In the long-term group, cytokine and chemokine levels in LPS-treated and DSP4+LPS-treated rats were returned to control levels, suggesting a resolution of inflammation after seven days. While previous studies showed increased hippocampal IL-1β levels after LPS exposure in rats [ 65 , 66 ], this was not the case under our experimental conditions, possibly due to differences in animal models or incubation period between LPS administration and sample collection. It is also noteworthy that the LPS dose used in our study (0.75 mg/kg) was lower than the ones used in the Fu et al [ 65 ] (2 mg/kg) and Kawano et al [ 66 ] (5 mg/kg) studies.…”
Section: Discussioncontrasting
confidence: 86%
“…While previous studies showed increased hippocampal IL-1β levels after LPS exposure in rats [ 65 , 66 ], this was not the case under our experimental conditions, possibly due to differences in animal models or incubation period between LPS administration and sample collection. It is also noteworthy that the LPS dose used in our study (0.75 mg/kg) was lower than the ones used in the Fu et al [ 65 ] (2 mg/kg) and Kawano et al [ 66 ] (5 mg/kg) studies. However, we found that the NE lesion caused by the DSP4 toxin resulted in significantly elevated hippocampal IL-1β levels 4 hours after the LPS administration.…”
Section: Discussioncontrasting
confidence: 86%
“…Studies in rodents have shown that attenuation of neuroinflammation in the hip pocampus after MCAO, for example, by exposure of ani mals to an enriched environment [40] or administration of insulin like growth factor 1 [41] improves ischemia induced cognitive deficits. On the contrary, activation of neuroinflammation by LPS resulted in memory loss, which was observed seven days [42] and even ten months [43] after a single administration of endotoxin, and reli ably correlated with the increased levels of the pro inflammatory cytokines TNF α and IL 1β in the hip pocampus.…”
Section: Role Of Neuroinflammation In Post Stroke Disordersmentioning
confidence: 99%
“…Five presenters presented their own most recent research outcomes and reviewed related publications. Takashi Kawano explained that postoperative delirium and POCD are closely related, and both are the result of an inflammatory reaction in the nervous system [28,29]. He also reported that postoperative pain management and intensive early rehabilitation seem to be important for the prevention of POCD in elderly patients.…”
Section: Journal Of Anesthesia Symposium 2016mentioning
confidence: 99%